(untitled) (International journal of artificial intelligence, 2025)
Ischemic stroke is one of the most pressing issues in modern medicine, and its early diagnosis plays a crucial role in preserving patients’ quality of life and reducing complications. Neuroimaging methods, including computed tomography (CT) and magnetic resonance imaging (MRI), are considered key diagnostic tools in the early detection of stroke. CT provides rapid results in differentiating between hemorrhagic and ischemic types during the acute stage, while MRI demonstrates high sensitivity in identifying small lesions and early changes in brain tissue. This article analyzes the clinical significance of ischemic stroke, the role of neuroimaging in its early diagnosis, and the capabilities of CT and MRI based on modern scientific literature.